Assessment of the Water Quality of Jatiluhur Reservoir, the Downstream of Citarum Cascade River, Using Selected Physico-Chemical Parameters - Corsita, Lieza; Arwin, Arwin; Muntalif, Barti Setiani; Salami, Indah Rachmatiah (Jurnal Rekayasa Kimia & Lingkungan, 2014)
Physico-chemistry and biological data were investigated from October 2010 until April 2011 of Jatiluhur reservoir. A total of six sampling stations were selected for this study. The discharge and hidrological data were obtained from Perum Jasa Tirta II Jatiluhur. The results showed that the hydrological regime in the reservoir Jatiluhur was affected by global phenomenon La Nina events in 2010 and early in 2011. Stream flows were determined during sampling to range from 78 to 482.5 m3/s. The water quality findings were as follows: pH (6.93-8.81), temperature (26.37-30.6C), dissolved oxygen (0.733-5.2 mg/l), conductivity (2.45-233mhos/cm), COD (7.36-96.9 mg/l), turbidity (4.063-65.6 NTU), total phosphate (0.002-0.324 mg/l), total nitrogen (0.99-5.96 mg/l), chlorophyl (2.237-43.37 mg/m3), visibility (30-160 cm). The eutrophication was pronounced at Jatiluhur reservoir. Canonical Correspendence Analysis found that some water quality parameters correlated positively with the discharge and the water level.